Midwifery and Nursing Students’ Communication Skills and Life Orientation: Correlation with Stress Coping Approaches - Özdemir, Gülsün (Nurs Midwifery Stud, 2013)
BACKGROUND: Methods learnt by nursing and midwifery students’ such as communication skills, optimisim and coping with stress would be used in their profeesional life. It is very important to promote their positive thinking and communication skills to raise coping with stress. OBJECTIVES: This cross sectional study was performed to examine the nursing and midwifery students’ communication skills and optimistic life orientation and its correlation with coping strategies with stress. MATERIALS AND METHODS: The study population included 2572 students who were studying in departments of nursing and midwifery in Istanbul. The sample was included 1419 students. Three questionnaires including Communication Skills Test, Life Orientation Test and Ways of Coping Inventory were used for data collection. The data were evaluated by calculating frequency, percentage, arithmetic mean, standard deviation and Pearson correlation coefficient. RESULTS: Students’ total mean score from the Communication Skills Scale was 165.27 ± 15.39 and for the Life Orientation Test was 18.51 ± 4.54. There was a positive correlation between their Life Orientation scores and the scores for self confidence (r = 0.34, P < 0.001), optimistic approach (r = 0.42, P < 0.001), and seeking social help (r = 0.17, P < 0.001). Also there was a significant positive correlation between Communication skill scores and self confidence (r = 0.46, P < 0.001), optimistic (r = 0.37, P < 0.001) and seeking social help approaches (r = 0.29, P < 0.001), but there was a significant negative correlation between communication skill scores and scores for helpless (r = -0.29, P < 0.001) and submissive approaches (r = -0.36, P < 0.001). CONCLUSIONS: As scores of students in optimistic life orientation and communication skills increased self confidence approach, optimistic, and social support seeking scores increased, whereas helpless, and submissive scores decreased.